Standards of genetic testing in the diagnosis and prognostication of systemic mastocytosis in 2022: recommendations of the EU-US Cooperative Group - Hoermann, Gregor; Sotlar, Karl; Jawhar, Mohamad; Kristensen, Thomas; Bachelot, Guillaume; Nedoszytko, Boguslaw; Carter, Melody C.; Horny, Hans-Peter; Bonadonna, Patrizia; Sperr, Wolfgang R.; Hartmann, Karin; Brockow, Knut; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Mastocytosis comprises rare heterogeneous diseases characterized by an increased accumulation of abnormal mast cells in various organs/tissues. The pathogenesis of mastocytosis is strongly linked to the presence of KIT-activating mutations. In systemic mastocytosis (SM), the most frequent mutation encountered is KIT p.D816V, whose presence constitutes one of the minor diagnostic criteria. Different techniques are used to search and quantify the KIT p.D816V mutant; however, allele-specific quantitative PCR and droplet digital PCR are today the most sensitive. The analysis of the KIT p.D816V allele burden has undeniable interest for diagnostic, prognostic, and therapeutic monitoring. The analysis of non-mast cell hematological compartments in SM is similarly important because KIT p.D816V multilineage involvement is associated with a worse prognosis. In addition, in advanced forms of SM, mutations in genes other than KIT are frequently identified and affect negatively disease outcome and response to therapy. Thus, combined quantitative and sensitive analysis of KIT mutations and next-generation sequencing of other recurrently involved myeloid genes make it possible to better characterize the extent of the affected cellular compartments and additional molecular aberrations, providing a more detailed overview of the complex mutational landscape of SM, in relation with the clinical heterogeneity of the disease. In this article, we report the latest recommendations of the EU-US Cooperative Group presented in September 2020 in Vienna during an international working conference, on the techniques we consider standard to detect and quantify the KIT p.D816V mutant in SM and additional myeloid mutations found in SM subtypes.
Online verfügbar: 11. März 2022, Artikelversion: 9. August 2022
Gesehen am 23.10.2023